Research on Vibration Reduction Design of Foundation with Entangled Metallic Wire Material under High Temperature - Yue Zhu; Yiwan Wu; Hongbai Bai; Zheyu Ding; Yichuan Shao (Shock and Vibration)
When the submarine is sailing at full speed, the power cabin has an abnormally high temperature. However, in the previous research on the vibration reduction design of the foundation, the influence of high temperature on the vibration characteristics of the foundation is not taken into account. In this paper, a new composite foundation with entangled metallic wire material (EMWM) is presented to reduce the vibration of the foundation. The energy transfer path of the foundation was obtained by the power flow method, and then the layout of EMWM was determined. The optimization of the constraining layer was carried out by modal analysis. The damping performance of the composite foundation with EMWM was validated by the thermal-vibration joint test. The results show that, at room temperature, the composite foundation has remarkable vibration reduction efficiency in the middle and high-frequency bands. The maximum insertion loss can reach 15.37 dB. The insertion loss varies with the location of the excitation point. As the temperature rises to 300°C, the insertion loss in the low-frequency band was improved, and the insertion loss is not influenced by the excitation position.